Gambaran Motivasi Warga Belajar Pelatihan Keterampilan Menyulam Selendang Koto Gadang di PKBM Anarvani Padang - Safitri, Vina; Syuraini, Syuraini (Penerbit Aksara Rentaka Siar (ARS), 2019)
This research was motivated by the high motivation of the learning community in skills training to embroider the Koto Gadang scarf at PKBM Anarvani Padang. One of the causes of the high motivation of the learning community is the high success of learning residents who have opened their own businesses. The purpose of this research is to get information about the success of the learning community of skills training in embroidering the Koto Gadang shawl at PKBM Anarvani Padang. This research is a quantitative descriptive study. The population of this study is training learning residents who follow the skills of embroidering Koto Gadang scarves in PKBM Anarvani in 2018, totaling 10 people, all populations were appointed as respondents. The technique used is using census techniques. Data collection techniques spread questionnaires. The results of this study indicate that the success of the learning population of the Koto Gadang scarf embroidery skills training is high.